Protecting Benzylic CH Bonds by Deuteration Doubles the Operational Lifetime of Deep‐Blue Ir‐Phenylimidazole Dopants in Phosphorescent OLEDs. Issue 16 (18th May 2021) - Bae, Hye Jin; Kim, Jong Soo; Yakubovich, Alexander; Jeong, Jinhoon; Park, Sangho; Chwae, Jun; Ishibe, Satoko; Jung, Yongsik; Rai, Virendra Kumar; Son, Won‐Joon; Kim, Sunghan; Choi, Hyeonho; et al.
Abstract: Much effort has been dedicated to increase the operational lifetime of blue phosphorescent materials in organic light‐emitting diodes (OLEDs), but the reported device lifetimes are still too short for the industrial applications. An attractive method for increasing the lifetime of a given emitter without making any chemical change is exploiting the kinetic isotope effect, where key CH bonds are deuterated. A computer model identifies that the most vulnerable molecular site in an Ir‐phenylimidazole dopant is the benzylic CH bond and predicts that deuteration may hamper the deactivation pathway involving CH/D bond cleavage notably. Experiments show that the device lifetime until the initial luminance diminishes to 70% (LT70 ) of a prototype phosphorescent OLED device can be doubled to 355 hours with a maximum external quantum efficiency of 25.1% at 1000 cd m −2 . This is one of the best operational performances of blue phosphorescent OLEDs observed to date in a single stacked cell. Abstract : The operational lifetime of blue emitters in organic light‐emitting diodes (OLEDs) is usually short, demanding a novel design strategy. Here, the kinetic isotope effect was used to double the operational lifetime of deep‐blue phenylimidazole‐based iridium(III) dopants. The longer device lifetime is due to the protection of benzylic CH bonds, which are proposed to participate in the degradation.